KEBIJAKAN PEMERINTAH DALAM PENYEDIAAN ASRAMA DI MADRASAH ALIYAH NEGERI PROGRAM KEAGAMAAN (MAN-PK) - Ayu Puspitasari; Yuni Aprilianti; Muchammad Eka Mahmud (Universitas Negeri Gorontalo, 2023)
Dormitories are one of the important means of creating guidance so that religious life can be realized. And Madrasah Aliyah Negeri Religious Program is one of the boarding-based schools that instills religious values in its activities. Madrasah Aliyah religious program administrators are required to have a dormitory as a place for students to live while studying at the madrasah. Therefore, the provision of infrastructure, especially dormitories, is an important factor in the implementation of religious learning at the Madrasah Aliyah Religious Program. Therefore, the purpose of writing this article is to seek government policy to accommodate the provision of infrastructure, especially the provision of dormitories. The research method used is a qualitative method with a descriptive approach. The results of this study include: (1). Building dormitories by budgeting on a priority scale considering the availability of dormitories is an absolute requirement for the implementation of the MAN-PK program; (2). Strengthening regulations and collaboration in local government regarding the provision of dormitories in MAN; (3). Establish communication and mutual collaboration with parents of students in contributing to voluntary costs; (4). Collaborate and empower stakeholders and education observers regarding the construction of dormitories at MAN-PK; (5). Collaborating with madrasas to procure infaq programs for students to assist in providing dormitories at MAN-PK.